Exploring EFL Teachers’ TPACK Implementation in Rural Indonesia: Insights from Central Kalimantan - Dellis Pratika; Emeral Emeral; Novika Amalia; Tampung Nias Saman; Julianthi Zefana Silitonga; Misericordias Domini (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study investigates Indonesian EFL teachers’ perceptions and implementation of Technological Pedagogical Content Knowledge (TPACK) in rural Central Kalimantan. Using a qualitative design with semi-structured interviews, it explores how teachers integrate content, pedagogy, and technology in their classroom practices. The findings show that teachers demonstrate strong confidence in content and technological knowledge, adapting instruction to students’ needs and displaying positive attitudes toward technology integration. However, challenges persist in pedagogical domains, particularly in fostering collaboration, and are compounded by infrastructural limitations, digital inequities, and restrictive institutional policies. This study highlights rural teachers’ adaptive strategies under constrained conditions, expanding TPACK beyond urban settings. The implications call for teacher training that emphasizes pedagogically grounded and context-sensitive approaches, and for policies that strengthen rural digital infrastructure and promote equitable access. Future research should broaden the extent to a broader rural context, include learner perspectives, and examine teachers’ sustainable TPACK development.